2020
DOI: 10.1590/s0102-865020200010000004
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine protects intestine against ischemia-reperfusion injury by alleviating endoplasmic reticulum stress induced apoptosis in rats

Abstract: Purpose: Glutamine, as an essential part of enteral nutrition and parenteral nutrition agent, has been widely recognized to be a kind of important intestinal mucosa protectant in clinical practice and experimental research. However, the mechanisms of its protective effects are still not fully understand. Consequently, this study aimed to explore the potential mechanism of glutamine on ischemia-reperfusion (I/R) injury induced endoplasmic reticulum (ER) stress in intestine.Methods: An experimental model of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Some studies have found that Asp pretreatment can alleviate oxidative stress in myocardial infarction (MI)-induced rats by increasing the levels of glutathione and mitochondrial adenine nucleoside triphosphate (ATP) while decreasing the level of lipid peroxides [9]. Other studies have suggested that Asp supplementation attenuates endoplasmic reticulum stress and cell apoptosis in trinitro-benzene-sulfonic acid-induced colitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that Asp pretreatment can alleviate oxidative stress in myocardial infarction (MI)-induced rats by increasing the levels of glutathione and mitochondrial adenine nucleoside triphosphate (ATP) while decreasing the level of lipid peroxides [9]. Other studies have suggested that Asp supplementation attenuates endoplasmic reticulum stress and cell apoptosis in trinitro-benzene-sulfonic acid-induced colitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…34) Calpastatin overexpression protects against traumatic spinal cord injury, 35) and calpain knock-out attenuates acute kidney injury. 30) CVB3 infection could induce calcium overload. 36) Excessive calcium induces calpain activation.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain inhibition suppressed ER stress in CVB3infected mice: GRP78 is an important component in ER, widely used as a marker of ER stress. 30) Thus, we tested the expression of GRP78 in heart tissues of VMC mice. The result exposed that CVB3 infection increased the GRP78 in the virus group, suggesting that CVB3 infection triggered ER stress in VMC mice.…”
Section: Calpain Inhibition Ameliorates Cvb3-induced Myocardium Injurymentioning
confidence: 99%
“…Preserving and restoring the integrity of the mucosal barrier is crucial to minimize the harmful effects of IIR injury. Various amino acids, including arginine, glutamine, and citrulline, have been known for their trophic and cytoprotective effects on gut mucosal mass and integrity in IIR animals [6][7][8]. Evidence indicates that oxidative stress plays a key role in the pathogenesis of IIR injury [3].…”
Section: Introductionmentioning
confidence: 99%